AGRARIAN REFORM AS A HUMAN RIGHTS IMPERATIVE: BRIDGING INEQUALITY AND JUSTICE IN LAND DISTRIBUTION - Arisaputra, Muhammad Ilham; Ashri, Abdul Munif (Faculty of Law, Universitas Diponegoro, 2025)
This study investigates the connection between agrarian reform and human rights, exploring how agrarian reform, as a strategy to address structural inequalities in land distribution, is fundamentally linked to human rights principles. Through a normative approach incorporating statutory, theoretical, and philosophical analyses, this research highlights that agrarian reform is not merely a policy choice but an obligation for States, stemming from their duty to uphold the human right to land. International frameworks, including the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP 2007) and the United Nations Declaration on the Rights of Peasants (UNDROP 2018), recognize the right to land as a central element of human rights. In the context of Indonesia, where land inequality remains a significant issue, agrarian reform is essential for achieving social justice and redressing historical injustices, particularly for marginalized groups such as peasants and Indigenous peoples. The study argues that agrarian reform should not be viewed merely as land redistribution but as a broader effort to promote human dignity, equality, and prosperity, thus aligning with the principles of social justice and the State’s responsibility to ensure equitable land access. This research contributes to the understanding of agrarian reform as a human rights imperative, offering insights into its theoretical underpinnings and practical implications for legal and policy reforms.